Scrapbook Learning Media On The National Diversity Material And Religion In My Country For Class IV Elementary Students - Palicida, Viona Quiteria; Ayu, Imelda Ratih; Rohana (Perspektif Pendidikan dan Keguruan, 2023)
This study aims to produce scrapbook learning media development products on ethnic and religious diversity in my country that meet valid, practical, and effective criteria. This research uses a type of development research (research and development). The development model in this study refers to the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation and evaluation. The subject of this research was class IV of SD Negeri 32 Palembang. The data were obtained from validation questionnaires, student response questionnaires, teacher response questionnaires and proficiency tests. The results of the study were based on a validation questionnaire from a team of experts who assessed in terms of media display, presentation of material and language use which overall obtained a percentage score of 81.9% with a very valid category. The overall student practicality questionnaire obtained a percentage score of 94.66% and the overall teacher practicality questionnaire obtained a percentage score of 93.25% with a very practical category. The results of the overall effectiveness of students obtained a score of 82.04% obtained from the test of understanding the material of ethnic and religious diversity in my country with a very effective category. Based on the results developed by researchers entitled Scrapbook learning media development of material on the Diversity of Ethnicities and Religions in My Country for grade IV elementary school students, it is concluded that the scrapbook that has been developed has met the criteria of valid, practical and effective.